Inovasi Media Daur Ulang untuk Mengatasi Keterbatasan Alat Peraga di SD Sarmi - Golden R.SC. Ayomi; Chelsi Yuliana S; Suwita Suwita; Mamberuman Marthen Inggamer; Sara Ohee (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Limited availability of science (IPA) teaching aids in underdeveloped Papuan schools, such as YPK Ebenhaezer Yamna Elementary, significantly hinders meaningful scientific education. Primary challenges include a lack of functional facilities, low teacher innovation, infrastructure constraints, and a critical literacy crisis among students. This community service initiative aims to empower educators through workshops focused on creating independent science (IPA) tools from local inorganic waste to bridge facility gaps. The methodology employs training and simulations within a Participatory Action Learning System framework. Conducted between April 19–25, 2026, in the East Coast District, the program involved 10 teachers and 17 fifth-grade students. Results demonstrated the successful creation of three recycled teaching kits. Teacher competence improved by 97.1%, particularly among honorary staff. Students showed significant cognitive growth, with average scores rising from 54.1 to 78.2, achieving full mastery. This program effectively shifts teacher orientation from factory-made dependence toward creative independence using local resources.